Transcending the Discourse of Accuracy in the Teaching of Translation: Theoretical Deliberation and Case Study - Zhong, Yong (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractThe practice of translation in China and Australia has been influenced by a discourse of accuracy, which requires translations to be accurate, faithful, objective and impartial, etc. In the teaching of translation, this discourse has translated into a pedagogy that is centred on rules (i.e., criteria, standards and authority), that tends to rely on mechanical drills to enforce those rules and that dis-empowers students by turning them into innocent precision instruments. In three sections, the author of this article will discuss how he has been inspired by recent critical theories to reorient his teaching out of the discourse of accuracy.